Inventory of population projects in developing countries around the world. - United Nations Fund for Population Activities; United Nations Population Fund. ([New York] United Nations Fund for Population Activities, 1997)
Annual
"Multilateral assistance, bilateral assistance, non-governmental organization assistance."
Issued every 3 years as v. 2 of: Population programmes and projects.
Vols. for 1988/1989- issued by the Fund under its later name: United Nations Population Fund.
Keywords: Birth control -- Directories; Population policy -- Periodicals; Population research -- Directories; Developing countries -- Population policy -- Periodicals